c - McConnell, Douglas [1951- ] (Grand Rapids, Michigan : Baker Academic, a division of Baker Publishing Group, 2018)
This volume helps leaders and leaders-in-training become students of culture who can then contextualize what they learn for their own organizational settings. Douglas McConnell, a respected leader in the worlds of missiology and higher education, enables readers to understand intercultural dynamics so they can shape their organizational cultures and lead their organizations in a missional direction. This is the latest volume in an award-winning series emphasizing mission as partnership with Christians around the globe. -- From publisher's description.
Thinking missiologically: implications for leadership and organizations -- Culture and human nature: the complex unity of human organizations -- Caring about members and others as people: notions of self and others -- Learning culture naturally: imitation and rituals -- Authority and culture: whom do you trust? -- Intercultural realities: four worlds of Christian organizations -- Leading in context: cultural influence and intercultural leadership -- Responding missionally: learning into practice.
Includes bibliographical references and index.
Keywords: Christianity and culture; Christian leadership; Missions